Acetobacter vaccinii sp. nov., a novel acetic acid bacterium isolated from blueberry fruit (Vaccinium corymbosum L.). Issue 11 (29th November 2022) - Heo, Jun; Sombolestani, Atena Sadat; Laureys, David; De Clippeleer, Jessika; Won, Miyoung; Vandamme, Peter; Kwon, Soon-Wo
Abstract : Strain C17-3 T was isolated from blueberry fruits collected from a farmland located in Damyang-gun, Jeollanam-do, Republic of Korea. Phylogenetic analysis based on 16S rRNA gene sequences allocated strain C17-3 T to the genus Acetobacter, where it occupied a rather isolated line of descent with Acetobacter ghanensis 430A T and Acetobacter lambici LMG 27439 T as the nearest neighbours (98.9 % sequence similarity to both species). The highest average nucleotide identity and digital DNA–DNA hybridization values were 76.3 % and 21.7 % with Acetobacter garciniae TBRC 12339 T ; both values were well below the cutoff values for species delineation. Cells are strictly aerobic, Gram-stain-negative rods, catalase-positive and oxidase-negative. The DNA G+C content calculated from the genome sequence was 59.2 %. Major fatty acids were summed feature 8 (C18 : 1 ω6 c and/or C18 : 1 ω7 c ) and C19 : 0 cyclo ω8 c . The major isoprenoid quinone was ubiquinone 9. On the basis of the results of phylogenetic analyses, phenotypic features and genomic comparisons, it is proposed that strain C17-3 T represents a novel species of the genus Acetobacter and the name Acetobacter vaccinii sp. nov. is proposed. The type strain is C17-3 T (= KACC 21233 T = LMG 31758 T ).